2017
DOI: 10.1038/oncsis.2017.65
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2-Keap1 pathway promotes cell proliferation and diminishes ferroptosis

Abstract: Cancer cells are hallmarked by high proliferation and imbalanced redox consumption and signaling. Various oncogenic pathways such as proliferation and evading cell death converge on redox-dependent signaling processes. Nrf2 is a key regulator in these redox-dependent events and operates in cytoprotection, drug metabolism and malignant progression in cancer cells. Here, we show that patients with primary malignant brain tumors (glioblastomas, WHO °IV gliomas, GBM) have a devastating outcome and overall reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
353
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(371 citation statements)
references
References 47 publications
(58 reference statements)
16
353
0
2
Order By: Relevance
“…Those molecular targets of ginger indicate that it may have the potential for preventing and treating GI cancer (Prasad and Tyagi, 2015b). Though the notion that Nrf2 inducers and/or Keap-1 suppressors may serve as promoters of cancer cell proliferation with increased resistance to ferroptosis cell death (Fan et al, 2017); ginger extract exerted an Nrf-2-inducing activity with concurrent inhibition of alpha-feto protein, proliferation marker, in all examined tissues and decline in oxidative and inflammatory markers, thus contributing to its chemoprevention activity probably via mechanism involving Nrf2/Keap1/ARE pathway. Therefore, further molecular investigation is warranted to outline ginger antioxidant/anti-inflammatory/anti-proliferative crosstalk mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Those molecular targets of ginger indicate that it may have the potential for preventing and treating GI cancer (Prasad and Tyagi, 2015b). Though the notion that Nrf2 inducers and/or Keap-1 suppressors may serve as promoters of cancer cell proliferation with increased resistance to ferroptosis cell death (Fan et al, 2017); ginger extract exerted an Nrf-2-inducing activity with concurrent inhibition of alpha-feto protein, proliferation marker, in all examined tissues and decline in oxidative and inflammatory markers, thus contributing to its chemoprevention activity probably via mechanism involving Nrf2/Keap1/ARE pathway. Therefore, further molecular investigation is warranted to outline ginger antioxidant/anti-inflammatory/anti-proliferative crosstalk mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Under normoxic cellular conditions, Nrf2 is bound by Kelch-like ECH-associated protein 1 (Keap1) and persists in an inactivated status through ubiquitination and degradation in the proteasome (Reisman et al, 2009). Upon oxidative or electrophilic stress, Nrf2 becomes unleashed from the Keap1 protein binding and translocates to the nucleus (Fan et al, 2017). In the nucleus, Nrf2 transcripts antioxidant responsive element (ARE)-dependent genes in order to balance oxidative mediators and maintain cellular redox homeostasis (Hayes and Dinkova-Kostova, 2014).…”
Section: Other Related Signaling Metabolismmentioning
confidence: 99%
“…The activity of Nrf2 is strictly regulated by Kelch-like ECH-related protein 1 (Keap1); Keap1 not only passively isolates Nrf2 from the cytoplasm but also plays an active role in targeting Nrf2 for ubiquitination and proteasome degradation (Zhang et al, 2004;Furukawa and Xiong, 2005). Nrf2 can directly or indirectly regulate GPX4 protein content (Hayes and Dinkova-Kostova, 2014;Fan et al, 2017;Dodson et al, 2019;Zhang et al, 2019), intracellular free iron content (Agyeman et al, 2012;Sun et al, 2016b;Shin et al, 2018), mitochondrial function (Merry and Ristow, 2016;Navarro et al, 2017), nicotinamide adenine dinucleotide hydro-phosphoric acid (NAPDH) regeneration (Abdalkader et al, 2018), etc., thereby regulating ferroptosis process. Of note, many studies found that Nrf2 is expressed in the central nervous system (CNS), neurons, astrocytes, leukocytes, and microglia (Tanaka et al, 2011;Dang et al, 2012;Sandberg et al, 2014), and numerous evidence suggests that Nrf2 plays an important role in the development and treatment of neurodegenerative diseases Deng et al, 2019;Jang et al, 2019;Pachón-Angona et al, 2019;Wei et al, 2019).…”
Section: Introductionmentioning
confidence: 99%